Consensus recommendations for the prevention of cervical cancer in Sub-Saharan Africa (2013)
Cervical cancer is the second most common cancer and the leading cause of cancer-related death in women in sub-Saharan Africa. It is estimated that more than 200 million females older than 15 years are at risk in this region. This paper highlights the current burden of cervical cancer in sub-Saharan Africa, reviews the latest clinical data on primary prevention, outlines challenges in the region, and offers potential solutions to these barriers. Based on these factors, clinical recommendations for the prevention of cervical cancer from the sub-Saharan African Cervical Cancer Working Group expert panel are presented.